Multi-criteria analysis of transport infrastructure projects - Broniewicz, Elzbieta; Ogrodnik, Karolina (Transportation research. Part D, Transport and environment, 2020)
•Transport infrastructure causes changes in almost every element of the environment.•SEA and EIA are the instruments of environmental impact assessment in the EU.•AHP and TOPSIS are the most popular methods for making decisions in SEA and EIA.•The fuzzy set theory is an important element of modern multi-criteria analyses. Planning, construction and operation of transport infrastructure are associated with a multitude of adverse effects on the environment. The Strategic Environmental Assessment (SEA) and Environmental Impact Assessment (EIA) are important legal instruments of the European Union's environmental policy that allows for identifying, predicting, preventing, and mitigating and or compensating for these adverse effects. As part of the environmental impact assessment, variants of planned activities and investment projects are considered in order to select the option, which is the most favourable from the environmental point of view. The primary goal of this work is to examine the possibility of using multi-criteria methods in order to select the route variant most favourable for the environment. In the first stage, a review of global literature from 2010 to 2019 was conducted on the subject of MCDM/MCDA (Multi-Criteria Decision Making/Multi-Criteria Decision Analysis) methods used in transportation. Based on the review, it was proven that the most popular methods used to solve multi-criteria decision problems in the field of transport are respectively: AHP with modifications, TOPSIS, DEMATEL, as well as methods encompassed in the so-called European trend, i.e. PROMETHEE and ELECTRE. Four selected methods were used in the empirical part of this work. They were used to select the variant of the expressway section in north-eastern Poland and compare the result of the analysis with the choice made in the analyzed environmental impact report.